(untitled) (Chemical Engineering Research Bulletin, 2008)
The historical development of chemical industry in Bangladesh during the past fifty years has been presented including existing predicaments and what are to be done to meet the challenge of the 21st century for the desired growth of the sector. Chemical Engineering Research Bulletin 11 (2007) 77-100